A bio-inspired LIDA cognitive-based Digital Twin architecture for unmanned maintenance of machine tools. (April 2023) - Lv, Jianhao; Li, Xinyu; Sun, Yicheng; Zheng, Yu; Bao, Jinsong
Highlights: Introduced the key features and three phases of the LIDA cognitive-based Digital Twin (DT) architecture. Proposed the main development process under the scenario of unmanned maintenance of machine tools. Validated the proposed cognitive DT in the unmanned fault diagnosis of a drilling platform. Abstract: Affected by COVID-19, the maintenance process of machine tools is significantly hindered, while unmanned maintenance becomes an emerging trend in such background. So far, three challenges, namely, the dependence on maintenance experts, the dynamic maintenance environments, and unsynchronized interactions between physical and information sides, exist as the main obstacles in its widespread applications. In order to fill this gap, a bio-inspired LIDA cognitive-based Digital Twin architecture is proposed, so as to achieve unmanned maintenance of machine tools through a self-constructed, self-evaluated, and self-optimized manner. A three phases process in the architecture, including the physical phase, virtual phase, and service phase, is further introduced to support the cognitive cycle for unmanned maintenance of machine tools. An illustrative example is depicted in the unmanned fault diagnosis on the rolling bearing of a drilling platform, which validates the feasibility and advantages of the proposed architecture. As an explorative study, it is wished that this work provides useful insights for unmanned maintenance of machine tools in a dynamic production environment.